Electromyography-informed musculoskeletal modeling provides new insight into hand tendon forces during tennis forehand - de Monsabert, B. G.; Herbaut, A.; Cartier, T.; Vigouroux, L. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Lateral epicondylitis, also known as tennis elbow, is a major health issue among tennis players. This musculo-skeletal disorder affects hand extensor tendons, results in substantial pain and impairments for sporting and everyday activities and requires several weeks of recovery. Unfortunately, prevention remains limited by the lack of data regarding biomechanical risk factors, especially because in vivo evaluation of hand tendon forces remains challenging. Electromyography-informed musculo-skeletal modeling is a noninvasive approach to provide physiological estimation of tendon forces based on motion capture and electromyography but was never applied to study hand tendon loading during tennis playing. The objective of this study was to develop such electromyography-informed musculo-skeletal model to provide new insight into hand tendon loading in tennis players. The model was tested with three-dimensional kinematics and electromyography data of two players performing forehand drives at two-shot speeds and with three rackets. Muscle forces increased with shot speed but were moderately affected by racket properties. Wrist prime extensors withstood the highest forces, but their relative implication compared to flexors depended on the player-specific grip force and racket motion strategy. When normalizing wrist extensor forces by shot speed and grip strength, up to threefold differences were observed between players, suggesting that gesture technique, for example, grip position or joint motion coordination, could play a role in the overloading of wrist extensor tendons. This study provided a new methodology for in situ analysis of hand biomechanical loadings during tennis gesture and shed a new light on lateral epicondylitis risk factors.